Positive electrode material and preparation method thereof, lithium battery and electric device
By preparing Lin(NixCoyMnzM1-xyz)O2 cathode material and using a specific preparation method, the problem of poor dispersion of single-crystal ternary cathode material was solved, thereby improving the electrochemical performance and safety of lithium batteries.
Patent Information
- Application Number
- CN202511062857.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-30
- Publication Date
- 2025-11-07
AI Technical Summary
The single-crystal ternary cathode materials used in existing lithium batteries have problems such as poor dispersion, insufficient dissociation, excessive agglomeration, uneven particle size distribution, and a large amount of fine powder, which affect the capacity and safety performance of lithium batteries.
Using Lin(NixCoyMnzM1-xyz)O2 cathode material, the particle dispersion, dissociation, agglomeration, and uniform particle size distribution are ensured by controlling the I50, D50, and D1 parameters. The preparation method includes mixing, primary sintering, ultrasonic treatment, and secondary low-temperature sintering to prepare a structurally stable cathode material.
It improves the energy density, initial charge/discharge capacity, rate performance, and cycle stability of lithium batteries, reduces the fine powder content, and improves compaction density and electrochemical performance.
Smart Images

Figure CN120914246A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the technical field of batteries, in particular, relates to a positive electrode material and a preparation method thereof, a lithium battery and an electric device. BACKGROUND
[0002] With the rapid development of the market of electronic equipment, electric vehicles, smart home, electric tools, intelligent transportation, etc., the demand for batteries is also increasing. As a kind of chemical power supply, lithium battery has the advantages of high energy density, wide working temperature range, long service and storage life, etc., and has strong advantages in energy storage, power and consumer batteries. It is one of the most popular chemical power supplies.
[0003] For lithium batteries, the currently widely used layered ternary positive electrode material has high reversible discharge capacity, and is a high-energy-density positive electrode material for lithium-ion batteries. Among them, the single-crystal ternary positive electrode material has good structural stability and rate performance, but the single-crystal positive electrode material obtained by fluidized bed airflow milling has poor dispersibility, insufficient dissociation, more agglomeration, uneven particle size distribution, and difficult particle size control. Excessive collision between particles can easily produce fine powder, thereby affecting the capacity and safety performance of lithium batteries. Therefore, the related technology of ternary positive electrode material still needs to be improved. SUMMARY
[0004] The present application aims to at least solve one of the technical problems in the related art. To this end, the present application provides a positive electrode material and a preparation method thereof, a lithium battery and an electric device. The positive electrode material has good particle dispersibility, sufficient dissociation, less agglomeration, uniform particle size distribution, and less fine powder. Using the positive electrode material in a lithium battery can greatly improve the electrochemical performance of the lithium battery.
[0005] In a first aspect of the present application, a positive electrode material is provided, comprising a compound represented by the following formula: Li n (Ni x Co y Mn z M 1-x-y-z )O2, wherein 0.95≤n≤1.15, 0.96≤x+y+z≤1, M is at least one of Al, Ce, Fe, P, W, Co, Mo, Sr, Sb, Ta, Nb, Y, Mg, Ti, Zr; and satisfies: 1.01≤I 50 =D 50 / p≤1.4; D1≥1.3μm, the particle size p is the average value of the micrometer caliper diameter of the positive electrode material measured in the SEM image.
[0006] Specifically, when the positive electrode material has agglomerated particles, the particle size of individual particles can be more accurately detected by SEM photos, and D 50D1 is more accurate to obtain the particle size of the agglomerated particles. In the positive electrode material of the present application, I 50 = D 50 / p is close to 1, indicating that the positive electrode material has good particle dispersibility, sufficient dissociation, less agglomeration, and uniform particle size distribution, and D1≥1.3μm indicates that 99% by volume of the particles in the positive electrode material have a particle size of 1.3μm or more, the content of fine powder in the positive electrode material is less, and the positive electrode material has a higher compaction density, and when used in a lithium battery, has a higher energy density, a higher initial charge and discharge capacity and efficiency, a better rate performance, and better cycle stability.
[0007] In some embodiments, the positive electrode material satisfies: 1.01≤I 50 = D 50 / p≤1.25; specifically, 1.01≤I 50 = D 50 / p≤1.15; and D1≥1.4μm. Thus, the positive electrode material has higher size uniformity, and the positive electrode material has higher structural stability, thereby improving the cycle stability and other electrochemical properties of the lithium battery.
[0008] In some embodiments, the positive electrode material satisfies: 0.1≤K 95 =(D 95 -D5) / D 50 ≤1.1, specifically, 0.3≤K 95 =(D 95 -D5) / D 50 ≤1.0; and more specifically, 0.6≤K 95 =(D 95 -D5) / D 50 ≤0.9. Thus, the particle size distribution of the positive electrode material is more uniform, thereby helping to improve the structural stability of the positive electrode material.
[0009] In some embodiments, the agglomeration rate of the positive electrode material is ≤8%, wherein the agglomeration rate is the ratio of the number of particles with ≥3 adherent particles to the total number of particles. Thus, the positive electrode material has good particle dispersibility, which helps to improve the structural stability of the positive electrode material.
[0010] In some embodiments, the particle size p and the particle size distribution of the positive electrode material satisfy: Specifically, More specifically, wherein, is the proportion of particles with a particle size distribution in the range of (p-p / 2, p+p / 2). Thus, the particle size distribution of the positive electrode material is more uniform, thereby making the positive electrode material have higher structural stability.
[0011] In some embodiments, the positive electrode material satisfies at least one of the following conditions:
[0012] D 99 ≤ 5.5 μm, specifically D 99 ≤ 4.5 μm;
[0013] D 50 is 1-10 μm, specifically 1 μm-5 μm, more specifically 1.6 μm-3.0 μm;
[0014] The particle size is 0.1 ≤ p ≤ 10 μm, specifically 0.5 ≤ p ≤ 6 μm, more specifically 1 ≤ p ≤ 2.4 μm;
[0015] The compaction density of the positive electrode material is 3.0 g / cm 3 - 3.75 g / cm 3 , specifically 3.2 g / cm 3 - 3.65 g / cm 3 ;
[0016] The alkali content is ≤ 10,000 ppm, specifically the alkali content is ≤ 6,000 ppm, more specifically the alkali content is ≤ 4,000 ppm. Thereby, the structural stability of the positive electrode material is further improved.
[0017] In some embodiments, at least one of the following conditions is satisfied: 1.01 ≤ n ≤ 1.09, 0.97 ≤ x + y + z ≤ 1, 0.6 ≤ x ≤ 0.98, 0.03 ≤ y ≤ 0.15, 0.1 ≤ z ≤ 0.3. Thereby, the various electrochemical performances of the positive electrode material are improved.
[0018] In a second aspect of the present application, a method for preparing the above positive electrode material is provided, comprising: mixing a nickel-cobalt-manganese precursor, a lithium source, and optionally a dopant to obtain a first mixture; performing primary sintering on the first mixture to obtain a primary sintered product; mixing the primary sintered product with water, and then performing ultrasonic treatment under stirring and drying to obtain an ultrasonic product; mixing the ultrasonic product with a coating agent to obtain a second mixture; performing secondary low-temperature sintering on the second mixture to obtain the positive electrode material; wherein the dopant contains M 1 elements, the M 1 elements include at least one of Al, Ce, Fe, P, B, W, Sr, Y, Mg, Ti, and Zr; and the coating agent contains M 2 elements, the M 2 elements include at least one of Al, W, Co, Mo, B, Sb, Ta, Nb, Mg, and Ti. The preparation method is simple in operation and low in energy consumption, and has high yield and is easy for industrial production.
[0019] In some embodiments, the first sintering satisfies at least one of the following conditions:
[0020] The temperature rising rate of the first sintering is 1-10°C / min, specifically 2-6°C / min;
[0021] The sintering temperature of the first sintering is 700-1100°C, specifically 750-940°C;
[0022] The sintering time of the first sintering is 3-15h, specifically 6-12h.
[0023] Thus, it is helpful to obtain a first sintering product with stable structure.
[0024] In some embodiments, the first sintering product is mixed with water and an auxiliary agent, and then the ultrasonic treatment and the drying are sequentially performed to obtain the ultrasonic product. Thus, it is helpful to improve the structural stability and electrochemical performance of the ultrasonic product.
[0025] In some embodiments, the ultrasonic treatment satisfies at least one of the following conditions:
[0026] The solid-liquid ratio of the first sintering product to water is 0.5-5:1, specifically 0.5-1.5:1;
[0027] The ultrasonic power is 100-3000W, specifically 1000-2500W;
[0028] The ultrasonic frequency is 10-50KHz, specifically 30-45KHz;
[0029] The temperature of the ultrasonic treatment is 10-60°C, specifically 20-40°C;
[0030] The time of the ultrasonic treatment is 10-80min, specifically 20-50min;
[0031] The stirring paddle rotation speed is 60-600rad / min, specifically 300-500rad / min;
[0032] The auxiliary agent includes at least one of an acidic detergent and the coating agent; the acidic detergent includes at least one of hydrochloric acid, phosphoric acid, metaphosphoric acid, oxalic acid and salts thereof, specifically at least one of hydrochloric acid, phosphoric acid, metaphosphoric acid, oxalic acid, sodium oxalate, ammonium metaphosphate, diammonium hydrogen phosphate and ammonium dihydrogen phosphate;
[0033] The molar ratio of the acidic detergent to the first sintering product is 0.0001-0.005:1;
[0034] The mass ratio of the coating agent to the primary product is 0-0.05:1. Thus, the primary product is fully dissociated, and the ultrasonic product is highly dispersed.
[0035] In some embodiments, the ultrasonic product satisfies at least one of the following conditions:
[0036] The D50 of the ultrasonic product is 1-10 μm, specifically 1-6 μm, more specifically 1.8-3.3 μm. 50
[0037] The tap density of the ultrasonic product is 3.0 g / cm3-3.65 g / cm3, specifically 3.2 g / cm3-3.55 g / cm3, more specifically 3.3 g / cm3-3.5 g / cm3. Thus, the ultrasonic product has a relatively concentrated particle size distribution and uniform particle dispersion. 3 3 3 3
[0038] In some embodiments, the secondary low-temperature sintering satisfies at least one of the following conditions:
[0039] The heating rate of the secondary low-temperature sintering is 1-10 ℃ / min, specifically 2-6 ℃ / min.
[0040] The sintering temperature of the secondary low-temperature sintering is 300-650 ℃, specifically 350-500 ℃.
[0041] The sintering time of the secondary low-temperature sintering is 3-12 h, specifically 5-10 h. Thus, the positive electrode material has a stable structure.
[0042] In some embodiments, at least one of the following conditions is satisfied:
[0043] The nickel-cobalt-manganese precursor includes Ni x Co y Mn z( (OH)2.
[0044] The D50 of the nickel-cobalt-manganese precursor is 1-5 μm, specifically 2.4-3.9 μm. 50
[0045] The BET of the nickel-cobalt-manganese precursor is 6-20 m 2 / g, specifically 8-15 m 2 / g. 2 2
[0046] The tap density of the nickel-cobalt-manganese precursor is 0.5 g / cm 3 ~ 5 g / cm 3 , specifically 1 g / cm 3 ~ 3 g / cm 3 ;
[0047] The lithium source includes at least one of LiOH, Li2CO3, Li2SO4, and LiCl;
[0048] The molar ratio of the nickel-cobalt-manganese precursor to the lithium source is 1:0.95~1.15, specifically 1:1.01~1.09;
[0049] The dopant includes at least one of oxides and hydroxides of M 1 elements, specifically at least one of aluminum oxide, aluminum hydroxide, boron oxide, tungsten oxide, strontium oxide, yttrium oxide, zirconium oxide, titanium oxide, and magnesium oxide;
[0050] The molar ratio of M 1 elements in the dopant to the nickel-cobalt-manganese precursor is 0~0.03:1, specifically 0.001~0.02:1;
[0051] The coating agent includes at least one of oxides, hydroxides, sulfates, and oxalates of the M 2 elements, specifically at least one of aluminum oxide, aluminum hydroxide, boron oxide, boric acid, cobalt oxide, tricobalt tetraoxide, cobalt hydroxide, tungsten oxide, tungstic acid, and magnesium hydroxide;
[0052] The molar ratio of M 2 elements in the coating agent to the nickel-cobalt-manganese precursor is 0~0.03:1, specifically 0.001~0.018:1. Thereby, it is further conducive to obtaining a positive electrode material with concentrated particle size distribution and excellent electrochemical performance.
[0053] In the third aspect of the present application, a lithium battery is provided, including the positive electrode material described above. Thereby, the lithium battery has excellent capacity stability and safety performance.
[0054] In the fourth aspect of the present application, an electric device is provided, including the positive electrode material or the lithium battery described above. Thereby, the electric device has high energy output and safety. BRIEF DESCRIPTION OF DRAWINGS
[0055] Figure 1 is a preparation flowchart of the positive electrode material of an embodiment of the present application.
[0056] Figure 2 is an SEM image of the positive electrode material of Embodiment 2 of the present application.
[0057] Figure 3 is a particle size distribution diagram of the positive electrode material of Example 2 of the present application.
[0058] Figure 4 is a SEM diagram of the positive electrode material of Comparative Example 2 of the present application.
[0059] Figure 5 is a particle size distribution diagram of the positive electrode material of Comparative Example 2 of the present application. DETAILED DESCRIPTION
[0060] Embodiments of the present application are described in detail below. The embodiments described below are exemplary and are intended to explain the present application, and cannot be understood as a limitation of the present application.
[0061] The present application is based on the following findings and recognitions of the inventors:
[0062] As described above, for lithium ion batteries, although the layered ternary positive electrode material is widely used due to its high energy density and high reversible discharge capacity, there are also some problems, for example, the radius of Ni ion is close to that of Li ion in the ternary positive electrode material, and there is a cation mixing phenomenon on the surface of the material, that is, Ni ion will occupy the site of Li ion, thereby destroying the structural order of the layered material, and the greater the concentration of nickel ion in the lithium layer, the more difficult it is for lithium to be deintercalated in the layered structure, resulting in poor electrochemical performance of the lithium battery, for example, the rate performance decreases when the lithium battery is charged and discharged, and this problem becomes more serious with the increase of Ni ion. Single crystal positive electrode material can effectively solve the above problems, because the single crystal positive electrode material has a single and complete crystal structure, and the atomic arrangement is more regular, thereby having high mechanical strength and structural stability, and the cation mixing phenomenon can be basically avoided during the cycle process, and at the same time, due to its high structural stability, cracks or particle breakage will not occur on the surface of the particles during the cycle, so it has stable electrochemical performance. However, the single crystal positive electrode material currently used also has many problems, for example, the particle size distribution of some single crystal positive electrode materials is wide and the particle dispersion is poor, which greatly affects the structural stability of the positive electrode material and the electrochemical performance of the lithium battery; in addition, the particles in some single crystal positive electrode materials are too fine, which is not conducive to the improvement of the compaction density, and at the same time, it is easy to have a side reaction with carbon dioxide and water vapor in the air to generate lithium hydroxide or lithium carbonate, resulting in an increase in the basic components of the generated positive electrode material, thereby affecting the electrochemical performance of the lithium battery.
[0063] To solve the above problems, the inventors propose a positive electrode material with stable structure, the particles in the positive electrode material have good dispersion, complete dissociation, less agglomeration, uniform particle size distribution, and less fine powder, and have excellent electrochemical performance when applied to lithium batteries.
[0064] Thus, in the first aspect of the present application, a positive electrode material is provided, comprising a compound represented by the following formula: Li n (Ni x Co y Mn z M 1-x-y-z )O2, wherein 0.95≤n≤1.15, 0.96≤x+y+z≤1, M is at least one of Al, Ce, Fe, P, W, Co, Mo, Sr, Sb, Ta, Nb, Y, Mg, Ti, Zr; and simultaneously satisfying: 1.01≤I 50 =D 50 / p≤1.4; and D1≥1.3 μm.
[0065] Herein, the particle size p is the average of the caliper diameter of the positive electrode material measured in the SEM image under the scale, and the caliper diameter is the average of the length and width of the smallest circumscribed rectangle of the positive electrode material particles. D 50 D50 refers to the particle size corresponding to the cumulative particle size distribution percentage of 50% of the material, and its physical meaning is that the particles with a particle size greater than it account for 50% by volume, and the particles with a particle size less than it also account for 50% by volume, so D 50 D50 is also called the median diameter or median particle size; and D1 refers to the particle size corresponding to the cumulative particle size distribution percentage of 1% of the material, and its physical meaning is that the particles with a particle size greater than it account for 99% by volume, and the particles with a particle size less than it account for 1% by volume. 50 D50 and D1 can be tested by a laser particle size analyzer.
[0066] Specifically, when the positive electrode material has agglomerated particles, the particle size of individual particles can be more accurately detected by the SEM image, while D 50 50 and D1 can more accurately obtain the particle size of the agglomerated particles. In the positive electrode material of the present application, I 50 =D 50 The value of D / p is close to 1, indicating that the particle dispersion of the positive electrode material is good, the dissociation is sufficient, the agglomeration is less, the particle size distribution is uniform, the particle size distribution is highly concentrated, the particles are round and the surface is smooth, which can improve the compaction density, and the completely dissociated positive electrode material particles can be in full contact with the electrolyte, so that the Li ions can be more fully deintercalated during the electrochemical reaction, which helps to improve the charge and discharge capacity and rate performance of the lithium battery using the positive electrode material; and D1≥1.3 μm indicates that 99% by volume of the particles in the positive electrode material have a particle size greater than or equal to 1.3 μm, and the content of fine powder in the positive electrode material is less, so that the positive electrode material has a higher compaction density, and when used in a lithium battery, has a higher energy density, better rate performance and better cycle stability. Moreover, the surface residual alkali of the positive electrode material is reduced, the structure is more stable, and the electrochemical performance of the positive electrode material, such as the initial charge and discharge capacity and efficiency, cycle stability and safety, is improved.
[0067] It is understandable that the above I 50 It is an indicator for measuring the particle dispersibility of cathode materials, I 50 The closer the value is to 1, the better the particle dispersion of the surface cathode material. In some embodiments, 1.01 ≤ I 50 ≤1.4, specifically, 1.01≤I 50 ≤1.25, more specifically, 1.01≤I 50 ≤1.15. As an example, I 50 Specifically, it can be 1.01, 1.03, 1.05, 1.07, 1.09, 1.11, 1.13, 1.15, 1.2, 1.25, 1.3, 1.35, 1.4, or a range between any two of them. 50 Within the above range, it is evident that the cathode material exhibits good particle dispersion, sufficient dissociation, minimal agglomeration, and uniform particle size distribution, thereby contributing to improved compaction density and overall electrochemical performance of the cathode material.
[0068] In some embodiments, the D of the positive electrode material 50 The diameter ranges from 1 μm to 10 μm, specifically from 1 μm to 5 μm, and more specifically from 1.6 μm to 3.0 μm. As an example, the Do of the cathode material... 50 Specifically, the micrometer size can be 1 μm, 1.6 μm, 1.7 μm, 1.8 μm, 1.9 μm, 2.0 μm, 2.1 μm, 2.2 μm, 2.3 μm, 2.4 μm, 2.5 μm, 2.6 μm, 2.7 μm, 2.8 μm, 2.9 μm, 3.0 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, or any two of these ranges. The Do of the cathode material... 50 Within the above range, the structural stability and excellent electrochemical performance of the cathode material can be basically guaranteed, and D can be largely avoided. 50 Excessive density slows down lithium-ion diffusion, reducing the capacity of lithium batteries, and also affects D. 50 The problem is that particles that are too small tend to agglomerate, which hinders lithium-ion diffusion and affects the performance of lithium batteries.
[0069] In some embodiments, the particle size p of the positive electrode material satisfies 0.1 μm≤p≤10 μm, wherein the particle size p is the average value of the caliper diameter of the positive electrode material measured in the SEM image under the scale, specifically, p satisfies 0.5 μm≤p≤6 μm, more specifically, p satisfies 1 μm≤p≤2.4 μm. As an example, the particle size p specifically can be 1 μm, 1.2 μm, 1.4 μm, 1.6 μm, 1.8 μm, 2.0 μm, 2.2 μm, 2.4 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm or a range between any two of them. When the particle size is within the above range, the structural stability and excellent electrochemical performance of the positive electrode material can be basically ensured, and the problem that the diffusion of lithium ions is affected due to the excessively large or small particle size, thereby affecting the electrochemical performance of the lithium battery, can be basically avoided.
[0070] In some embodiments, D1 of the positive electrode material satisfies D1≥1.3 μm, specifically, D1≥1.4 μm. When D1 of the positive electrode material satisfies the above requirement, it indicates that the content of fine powder in the positive electrode material is low, which is beneficial to improve the compaction density, and when applied to the lithium battery, the contact area with the electrolyte is small, which is helpful to reduce the probability of side reactions of the positive electrode material, thereby effectively improving the capacity and cycle stability of the lithium battery.
[0071] In some embodiments, D 99 ≤5.5 μm, specifically, D 99 ≤4.5 μm. As an example, D 99 of the positive electrode material specifically can be 5.5 μm, 5.0 μm, 4.5 μm, 4.0 μm, 3.5 μm, 3.0 μm, 2.5 μm, 2.0 μm, 1.5 μm or a range between any two of them, and D 99 When D 99 of the positive electrode material is within the above range, it indicates that the positive electrode material has less agglomeration and better particle dispersion, thereby being beneficial to improve the compaction density of the positive electrode material, and thereby being beneficial to improve the electrochemical performance of the lithium battery using the positive electrode material.
[0072] In this paper, D 99 refers to the particle size corresponding to the cumulative particle size distribution percentage of 99% of the material, and its physical meaning is that the particles with a particle size greater than it account for 1% by volume, and the particles with a particle size less than it account for 99% by volume. D 95 can be tested by using a laser particle size analyzer.
[0073] Further, K 95 of the positive electrode material is a quantitative index of the particle size distribution of the positive electrode material, which can represent the particle uniformity of the positive electrode material, and K 95 of the positive electrode material satisfies K 50 of the positive electrode material satisfies K 95satisfies 0.1≤K 95 ≤1.1, specifically, K 95 of the positive electrode material satisfies 0.3≤K 95 ≤1.0, more specifically, K 95 of the positive electrode material satisfies 0.6≤K 95 ≤0.9. As an example, K 95 of the positive electrode material can be specifically 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.65, 0.7, 0.75, 0.8, 0.85, 0.9, 1.0, 1.1, or a range between any two of them. K 95 Within the above range, the particle size distribution of the positive electrode material is narrow, the particle size uniformity is high, which is beneficial to improve the compaction density, and helps to achieve maximum structural stability, and basically can avoid the problems that K 95 is too large, resulting in a large difference in particle size in the positive electrode material, the diffusion speed of lithium ions is different in the charging and discharging process, and the polarization phenomenon is intensified, and K 95 is too small, resulting in increased difficulty and cost of preparation.
[0074] In some embodiments, the particle size p of the positive electrode material and the particle size distribution satisfy: p+p / 2) wherein, is the proportion of particles with a particle size distribution in the range (p-p / 2, p+p / 2), which corresponds to the proportion of the area of the particle size distribution curve of the positive electrode material in the total area in the range (p-p / 2, p+p / 2). In some embodiments, specifically more specifically As an example, may be specifically 0.86, 0.9, 0.96, 0.97, 0.98, 0.99, 1, or a range between any two of them. Within the above range, it indicates that the particle size of the positive electrode material is highly concentrated around the particle size p of the positive electrode material, and the particle size distribution is highly concentrated, which can further improve the particle uniformity of the positive electrode material, and helps to reduce the existence of particles with too large size and particles with too small size, thereby improving the structural stability of the positive electrode material, and basically can avoid the problems that K is too large, resulting in increased difficulty and cost of preparation, and is too small, resulting in reduced structural stability of the positive electrode material.
[0075] In some embodiments, the agglomeration rate of the positive electrode material is ≤8%, wherein the agglomeration rate is the ratio of the number of particles with ≥3 adhered particles to the total number of particles. Specifically, the agglomeration rate of the positive electrode material can be 8%, 7%, 6%, 5%, 4%, 3%, 2%, 1%, or a range between any two of them. An agglomeration rate within the above range indicates that the positive electrode material particles are uniformly dispersed, sufficiently dissociated, and relatively independent of each other, thereby facilitating the diffusion of lithium ions and improving the electrochemical performance of lithium batteries. It can basically avoid the problem of particle agglomeration caused by excessive agglomeration rate, affecting the diffusion of lithium ions, and leading to the reduction of the charge and discharge efficiency of lithium batteries.
[0076] In this document, the agglomeration rate of the positive electrode material can be obtained by counting the SEM image of the positive electrode material.
[0077] In some embodiments, the positive electrode material has a compaction density PD of 3.0 g / cm 3 ~ 3.75 g / cm 3 , and specifically 3.2 g / cm 3 ~ 3.65 g / cm 3 . For example, the compaction density of the positive electrode material can be 3.0 g / cm 3 , 3.1 g / cm 3 , 3.2 g / cm 3 , 3.25 g / cm 3 , 3.3 g / cm 3 , 3.35 g / cm 3 , 3.4 g / cm 3 , 3.45 g / cm 3 , 3.5 g / cm 3 , 3.55 g / cm 3 , 3.6 g / cm 3 , 3.65 g / cm 3 , 3.7 g / cm 3 , 3.75 g / cm 3 , or a range between any two of them. The compaction density of the positive electrode material within the above range can significantly improve the energy density of the lithium battery using the positive electrode material.
[0078] In some embodiments, the alkali content of the positive electrode material is ≤10000 ppm, specifically, the alkali content of the positive electrode material is ≤6000 ppm, more specifically, the alkali content of the positive electrode material is ≤4000 ppm. As an example, the alkali content of the positive electrode material can be 4000 ppm, 3500 ppm, 3000 ppm, 2500 ppm, 2000 ppm, 1500 ppm, 1000 ppm, or a range between any two of them. When the alkali content of the positive electrode material is within the above range, the structure is more stable, and the electrochemical performance of the lithium battery using the positive electrode material can be further improved, such as cycle stability and safety, and the problem of processing difficulty of the positive electrode slurry and the problem of deteriorating electrochemical performance caused by too high alkali content on the surface of the positive electrode material can be basically avoided.
[0079] In some embodiments, the positive electrode material can be a ternary positive electrode material, and the ternary positive electrode material can be an unmodified intrinsic ternary positive electrode material, or a ternary positive electrode material modified by doping and / or coating. In some embodiments, in addition to the core components Ni, Co, and Mn of the ternary positive electrode material, the positive electrode material can also have at least one of the doping and / or coating elements, such as Al, Ce, Fe, P, W, Co, Mo, Sr, Sb, Ta, Nb, Y, Mg, Ti, and Zr. To some extent, it helps to strengthen the structural stability of the positive electrode material, thereby further optimizing its electrochemical performance.
[0080] Specifically, n is the stoichiometric ratio of Li in the positive electrode material, and can be 0.95≤n≤1.15, specifically, 1.01≤n≤1.09. As an example, n can be specifically 0.95, 1, 1.01, 1.02, 1.03, 1.04, 1.05, 1.06, 1.07, 1.08, 1.09, 1.1, 1.12, 1.15, or a range between any two of them. Thus, it helps to ensure that the positive electrode material has excellent capacity performance; if n is too large, the Li in the positive electrode material can be too much, which can lead to oxygen atom escape at high temperature, thereby increasing the risk of thermal runaway; if n is too small, the Li in the positive electrode material can be too little, which can lead to unstable structure.
[0081] Ni in the above positive electrode material helps to improve the capacity of the positive electrode material, Co and Mn both help to improve the structural stability of the positive electrode material, x+y+z is the sum of the stoichiometric ratios of Ni, Co and Mn in the positive electrode material, specifically, 0.96≤x+y+z≤1, specifically, it can be 0.97≤x+y+z≤1. As an example, x+y+z can be specifically 0.96, 0.97, 0.98, 0.99, 1.0 or any range between any two of them. Further, the stoichiometric ratio of single elements of Ni, Co and Mn also has a certain influence on the performance of the positive electrode material, in some embodiments, 0.6≤x≤0.98, x can be specifically 0.6, 0.7, 0.8, 0.9, 0.98 or any range between any two of them, 0.03≤y≤0.15, y can be specifically 0.03, 0.05, 0.08, 0.1, 0.12, 0.15 or any range between any two of them, 0.1≤z≤0.3, z can be specifically 0.1, 0.15, 0.2, 0.25, 0.3 or any range between any two of them. Satisfying the above conditions, the positive electrode material can have higher structural stability and high capacity, when x+y+z<1, other components can be added according to actual needs to further improve the performance of the positive electrode material, for example, adding Al, Mg, Ti and other doping elements in the positive electrode material can further improve the structural stability and thermal stability of the positive electrode material.
[0082] In some embodiments, the positive electrode material is a single crystal positive electrode material. Thus, its structural stability can be further improved, and the rate performance is better, and when used in a lithium battery, better overall electrochemical performance can be obtained.
[0083] Currently, in the related art, the preparation of a positive electrode material with structural stability can be achieved by one-step sintering under high temperature conditions, and the sintered product is broken by a fluidized bed type air flow mill, but the particle size of the positive electrode material broken by the air flow mill is difficult to control, the particle size distribution is usually wide and the dispersibility of the particles is poor, and fine powder is easily generated by over-breaking, thereby the alkali content on the surface of the particles is easily increased due to side reactions, thereby affecting the electrochemical performance and safety performance of the material, and at the same time, the process is complex, the yield is low, and the energy consumption is high; in addition, in the related art, a molten salt assisted sintering method is used to prepare a positive electrode material, specifically, a low melting point molten salt is added during sintering, which can reduce the sintering temperature and act as a reaction solvent, so that the lithiation reaction is carried out in a liquid state, the ion diffusion rate is improved, and a positive electrode material with relatively good dispersibility can be sintered, but after the reaction, the excess molten salt needs to be washed away with water, and the amount of molten salt used is large, the cost is high, the process is complex, and it is difficult to be applied to industrial production, at the same time, part of the ions in the molten salt will diffuse into the particles during high temperature sintering, which will have a certain influence on the performance of the positive electrode material.
[0084] Based on the above understanding, the inventors consider developing a new preparation method of a positive electrode material, and the positive electrode material prepared by the method has good particle dispersity, less agglomeration, and less fine powder.
[0085] Therefore, in the second aspect of the present application, a method for preparing the positive electrode material is provided, referring to Figure 1 The method comprises:
[0086] S10: mixing a nickel-cobalt-manganese precursor, a lithium source, and optionally a dopant to obtain a first mixture.
[0087] In this step, the specific way of mixing the nickel-cobalt-manganese precursor, the lithium source, and the optional dopant is not particularly limited, for example, the mixing can be performed by a mixer, grinding, or the like.
[0088] It can be understood that the optional dopant means that the dopant can be selected to be added or not added in this step, that is, the first mixture can contain the dopant or can not contain the dopant, which is flexibly selected according to actual needs.
[0089] In some embodiments, when the dopant is not needed, the nickel-cobalt-manganese precursor and the lithium source can be mixed in a molar ratio of 1:0.95-1.15, specifically, the nickel-cobalt-manganese precursor and the lithium source can be mixed in a molar ratio of 1:1.01-1.09. Specifically, the molar ratio of the nickel-cobalt-manganese precursor and the lithium source can be 1:1.01, 1:1.02, 1:1.03, 1:1.04, 1:1.05, 1:1.06, 1:1.07, 1:1.08, 1:1.09, or any range between any two of the above ratios. The above ratio helps to obtain the first mixture with the target content of each element, so that the nickel-cobalt-manganese precursor fully undergoes lithiation reaction in the subsequent step, and a positive electrode material with better performance is obtained. If the above ratio is too large, too little lithium source may lead to insufficient lithiation reaction, and there are more un-lithiated nickel-cobalt-manganese precursor impurity phases, thereby affecting the structural stability of the subsequent material; if the above ratio is too small, too much lithium source may lead to increased cost.
[0090] In some embodiments, adding the dopant can further improve the structural stability of the positive electrode material. Specifically, the dopant contains M 1 elements, and the M 1 elements include at least one of Al, Ce, Fe, P, B, W, Sr, Y, Mg, Ti, and Zr. Therefore, the dopant can be mixed with the nickel-cobalt-manganese precursor and the lithium source at the same time to obtain the first mixture containing M 1 elements. The above dopant helps to further improve the electrochemical performance of the positive electrode material and the structural stability of the positive electrode material. Specifically, the dopant can be a compound containing M 1The at least one of the oxide and the hydroxide of the element can be at least one of aluminum oxide, aluminum hydroxide, boron oxide, tungsten oxide, strontium oxide, yttrium oxide, zirconium oxide, titanium oxide, and magnesium oxide. The above-mentioned dopant is widely available and low in cost, and has high solubility, which helps to mix uniformly with the nickel-cobalt-manganese precursor and the lithium source to obtain the first mixture.
[0091] In some embodiments, M 1 The molar ratio of the element to the nickel-cobalt-manganese precursor is 0-0.03:1, specifically 0.001-0.02:1. As an example, specifically, the molar ratio of M 1 The molar ratio of the element to the nickel-cobalt-manganese precursor can be 0.001:1, 0.005:1, 0.01:1, 0.015:1, 0.02:1, 0.025:1, 0.03:1, or any range between any two of them. Introducing a small amount of dopant helps to stabilize the structure of the target material in subsequent reactions, while optimizing the electrochemical performance of the target material. If the amount of dopant is excessive, it may increase the side reactions during the reaction process, and may also cause the structure of the target material to be distorted. If the amount of dopant is too small, it may not have an impact on the subsequent reaction and the target material, and may not play a role in stabilizing the structure. Too little dopant is also prone to uneven mixing.
[0092] In some embodiments, the lithium source includes at least one of LiOH, Li2CO3, Li2SO4, and LiCl. The above-mentioned lithium source is easy to ionize lithium ions, making the reaction proceed smoothly, while not introducing impurity ions; at the same time, the above-mentioned lithium source is widely available and easy to obtain, and is environmentally friendly.
[0093] In some embodiments, the D 50 of the nickel-cobalt-manganese precursor is 1-5 μm, specifically 2.4-3.9 μm. As an example, the D 50 of the nickel-cobalt-manganese precursor can be 1 μm, 1.5 μm, 2 μm, 2.4 μm, 2.6 μm, 2.8 μm, 3.0 μm, 3.2 μm, 3.4 μm, 3.6 μm, 3.8 μm, 3.9 μm, 4 μm, 4.5 μm, 5 μm, or any range between any two of them. The nickel-cobalt-manganese precursor as the initial raw material has a decisive role on the particle size of the subsequent product, and the D 50 Within the above range, it helps to more fully react with the lithium source in the subsequent steps, and helps to obtain the target particle size of the positive electrode material.
[0094] In some embodiments, the specific surface area (BET) of the nickel-cobalt-manganese precursor is 6-20 m 2 / g, specifically 8-15 m 2 / g, specifically 8-15 m 2 / g~15m 2 / g. As an example, the BET of the nickel cobalt manganese precursor can be specifically 8m 2 / g, 10m 2 / g, 12m 2 / g, 14m 2 / g, 15m 2 / g, 18m 2 / g, 20m 2 / g or a range between any two of them. The specific surface area within the above range helps to make the nickel cobalt manganese precursor more fully mixed with the lithium source and the dopant, and the uniformity of the obtained positive electrode material is better; if the specific surface area is too large, it can cause the nickel cobalt manganese precursor to have high surface energy and be prone to agglomeration; if the specific surface area is too small, it can cause the nickel cobalt manganese precursor to be insufficiently mixed with the lithium source and the dopant, and other problems.
[0095] In some embodiments, the tap density of the nickel cobalt manganese precursor is 0.5g / cm 3 ~5g / cm 3 , and can be specifically 1g / cm 3 ~3g / cm 3 . As an example, the tap density of the nickel cobalt manganese precursor can be 0.5g / cm 3 , 1g / cm 3 , 1.5g / cm 3 , 2g / cm 3 , 2.5g / cm 3 , 3g / cm 3 , 4g / cm 3 , 5g / cm 3 or a range between any two of them. The above tap density range is beneficial to obtaining a positive electrode material of a target particle size, and further improving the comprehensive performance of the positive electrode material.
[0096] In some embodiments, the nickel cobalt manganese precursor comprises Ni x Co y Mn z( OH)2. As an example, the nickel cobalt manganese precursor can be prepared by a coprecipitation method. Specifically, a soluble nickel salt, a cobalt salt and a manganese salt can be prepared into a mixed salt solution of metal ions with a concentration of 1mol / L~5mol / L according to the molar ratio of Ni:Co:Mn=x:y:z, and a complexing agent and a precipitating agent are added as raw materials into a reaction kettle with nitrogen as a protective gas, under the conditions of pH 9.5~13.0, temperature 30°C~60°C, and stirring rate 400rad / min~800rad / min for 5h~25h to obtain a precipitate, and then the precipitate is filtered, washed and dried to obtain a nickel cobalt manganese precursor powder.
[0097] Specifically, the concentration of the mixed metal ion salt solution can be 1 mol / L, 2 mol / L, 3 mol / L, 4 mol / L, 5 mol / L, or any range between any two of the foregoing concentrations, which helps to obtain a nickel-cobalt-manganese precursor powder with uniform particle size, and basically avoids the problems of low reaction efficiency caused by too low concentration of the mixed metal ion salt solution, and fast precipitation generation and easy agglomeration of the precipitate caused by too high concentration of the mixed metal ion salt solution. The pH of the reaction can be 9.5, 10.0, 10.5, 11.0, 11.5, 12.0, 12.5, 13.0, or any range between any two of the foregoing pH values, which helps the metal ions to react with the precipitant to generate the corresponding hydroxide precipitate, and basically avoids the problems of incomplete precipitation of metal ions caused by too low pH, and dissolution of metal hydroxide caused by too high pH. The reaction temperature can be 30°C, 35°C, 40°C, 45°C, 50°C, 55°C, 60°C, or any range between any two of the foregoing temperatures, which helps to promote the forward reaction and further improve the reaction rate, and basically avoids the problems of slow reaction rate caused by too low temperature, and increased cost caused by too high temperature. The stirring rate of the reaction can be specifically 400 rad / min, 450 rad / min, 500 rad / min, 550 rad / min, 600 rad / min, 650 rad / min, 700 rad / min, 750 rad / min, 800 rad / min, or any range between any two of the foregoing stirring rates, which helps to further improve the reaction speed and make the reaction proceed sufficiently, and basically avoids the problems of insufficient reaction caused by too low stirring rate, and high requirement for equipment caused by too high stirring rate. The reaction time can be specifically 5 h, 6 h, 8 h, 10 h, 12 h, 14 h, 16 h, 18 h, 20 h, 22 h, 24 h, 25 h, or any range between any two of the foregoing times, which helps to make the reaction sufficient, and basically avoids the problems of insufficient reaction caused by too short time, and time cost waste caused by too long time.
[0098] In some embodiments, the soluble nickel salt, cobalt salt, and manganese salt are common salts in the industry, which can be sulfate, carbonate, oxalate, chlorate, etc., and can be specifically NiSO4·6H2O, CoSO4·7H2O, MnSO4·H2O, etc. The foregoing salts have high solubility, are easy to dissolve and react, and have high purity, which helps to reduce impurities in the nickel-cobalt-manganese precursor powder, and the introduced anions can be removed by conventional washing and filtering methods.
[0099] In some embodiments, the precipitant is any one of the commonly used precipitants in the industry, such as sodium hydroxide, sodium carbonate, ammonium carbonate, ammonium bicarbonate, and specifically can be sodium hydroxide. Thus, it is helpful to react with the metal salt to generate a strong oxide precipitate. Further, the concentration of the sodium hydroxide solution is 2 mol / L to 8 mol / L, and specifically can be 2 mol / L, 3 mol / L, 4 mol / L, 5 mol / L, 6 mol / L, 7 mol / L, 8 mol / L, or a range between any two of them, which is helpful to fully precipitate the metal ions, reduce residues, improve the efficiency of the precipitation reaction, and basically avoid the problems of insufficient precipitation of metal ions due to too low concentration of the precipitant, and too fast precipitation generation rate and easy agglomeration due to too high concentration of the precipitant.
[0100] In some embodiments, the complexing agent is ammonia water, and the concentration of the ammonia water is 0.5 mol / L to 6 mol / L, and specifically can be 0.5 mol / L, 1 mol / L, 1.5 mol / L, 2 mol / L, 2.5 mol / L, 3 mol / L, 3.5 mol / L, 4 mol / L, 4.5 mol / L, 5 mol / L, 5.5 mol / L, 6 mol / L, or a range between any two of them. The complexing agent can control the speed of the precipitation of the metal salt in the above reaction by forming a complex with the metal ion, such as [Ni(NH3)6] 2+ , [Co(NH3)6] 2+ , etc. These complexes have certain stability, which slows down the reaction rate of the metal ion with the precipitant, so that the precipitation reaction can proceed more uniformly. Thus, the concentration of the ammonia water in the above range basically ensures that the above reaction proceeds uniformly, and basically avoids the problems of too slow precipitation speed due to too high concentration of the ammonia water, and too serious particle agglomeration due to too low concentration of the ammonia water.
[0101] S20: performing one-time sintering on the first mixture to obtain a one-time sintering product.
[0102] In this step, the above obtained first mixture can be subjected to one-time sintering under an air or oxygen atmosphere from room temperature to 700°C to 1100°C, and after sintering for 3 h to 15 h, it is cooled to room temperature to obtain the one-time sintering product.
[0103] In some embodiments, the first sintering has a heating rate of 1-10°C / min, and specifically 2-6°C / min. For example, the first sintering has a heating rate of 1°C / min, 2°C / min, 3°C / min, 4°C / min, 5°C / min, 6°C / min, 7°C / min, 8°C / min, 9°C / min, 10°C / min, or any range between any two of the aforementioned values. The heating rate in the above range helps to gradually transfer the heat inside the first mixture, and to make the temperature of each part of the first mixture uniform, thereby helping the reaction to proceed smoothly, and basically avoiding the problems of particle breakage caused by excessively high local temperature due to excessively fast heating rate, reduced structural stability of the first sintering product, and time waste caused by excessively slow heating rate.
[0104] In some embodiments, the first sintering has a sintering temperature of 700-1100°C, and specifically 750-980°C. For example, the first sintering has a sintering temperature of 700°C, 750°C, 800°C, 850°C, 900°C, 940°C, 1000°C, 1050°C, 1100°C, or any range between any two of the aforementioned values. The above temperature range helps the first mixture to react completely, and helps the lithium ions to be orderly inserted into the crystal lattice, and helps the nickel, cobalt, and manganese ions to stably occupy the corresponding crystal sites, thereby obtaining a first sintering product with stable structure, and basically avoiding the problems of cost waste caused by excessively high temperature and insufficient reaction of the first mixture caused by excessively low temperature.
[0105] In some embodiments, the first sintering has a sintering time of 3-15h, and specifically 6-12h. For example, the first sintering has a sintering time of 3h, 6h, 7h, 8h, 9h, 10h, 11h, 12h, 15h, or any range between any two of the aforementioned values. The above time basically ensures that the reaction proceeds sufficiently, and basically avoids the problems of insufficient reaction caused by excessively short time and time cost waste caused by excessively long time.
[0106] S30: mixing the first sintering product with water, and then performing ultrasonic treatment under stirring and drying to obtain an ultrasonic product.
[0107] In this step, the calcined product can be mixed with water in a solid-liquid ratio of 0.5-5:1, and then added to an ultrasonic washing container, and subjected to ultrasonic treatment under stirring for 10-80 min. After the ultrasonic treatment, the mixture is filtered, washed, and dried to obtain an ultrasonic product. Through the ultrasonic treatment, the calcined product can be effectively dissociated and dispersed, and the positive electrode material particles will not be excessively impacted to produce fine powder. Thus, the positive electrode material particles obtained have good dispersibility, less agglomeration, good uniformity of particle size, and are round and smooth in surface, which can improve the compaction density. Meanwhile, the completely dissociated positive electrode material particles are in full contact with the electrolyte, and the Li ions can be more fully deintercalated during the electrochemical reaction, which helps to improve the charge and discharge capacity and rate performance of the positive electrode material. After the water washing, the surface residual alkali of the calcined product is significantly reduced, the structure is more stable, and the electrochemical performance such as the cycle stability and safety of the positive electrode material can be improved.
[0108] In some embodiments, the calcined product can be mixed with water and an auxiliary agent, and then subjected to the above ultrasonic treatment and drying treatment under stirring to obtain an ultrasonic product. Specifically, the auxiliary agent can react with the residual alkali on the surface of the calcined product, thereby helping to further remove the residual alkali on the surface of the calcined product. Meanwhile, the auxiliary agent can be subjected to proton exchange with the surface of the calcined product particles, and subjected to complexation reaction with the metal ions in the calcined product, so that the surface of the calcined product particles is in a lithium-deficient state, which helps to improve the electrochemical performance of the positive electrode material.
[0109] In some embodiments, the auxiliary agent can include at least one of an acidic detergent and a coating agent. The acidic detergent can include at least one of hydrochloric acid, phosphoric acid, metaphosphoric acid, oxalic acid, and salts thereof, and specifically can be at least one of hydrochloric acid, phosphoric acid, metaphosphoric acid, oxalic acid, sodium oxalate, ammonium metaphosphate, diammonium hydrogen phosphate, and ammonium dihydrogen phosphate. The coating agent can include at least one of oxides, hydroxides, sulfates, and oxalates of elements M 2 The elements can specifically include at least one of Al, W, Co, Mo, B, Sb, Ta, Nb, Mg, and Ti, and thus the coating agent can specifically include at least one of aluminum oxide, aluminum hydroxide, boron oxide, boric acid, cobalt oxide, tricobalt tetraoxide, cobalt hydroxide, tungsten oxide, tungstic acid, and magnesium hydroxide. 2 The elements can specifically include at least one of Al, W, Co, Mo, B, Sb, Ta, Nb, Mg, and Ti, and thus the coating agent can specifically include at least one of aluminum oxide, aluminum hydroxide, boron oxide, boric acid, cobalt oxide, tricobalt tetraoxide, cobalt hydroxide, tungsten oxide, tungstic acid, and magnesium hydroxide.
[0110] In some embodiments, the molar ratio of the acidic detergent to the calcined product is 0.0001-0.005:1, specifically 0.0001:1, 0.0005:1, 0.001:1, 0.002:1, 0.003:1, 0.004:1, 0.005:1, or any range between any two of them. When the molar ratio is within the above range, the removal effect of residual alkali on the surface of the calcined product is better, which is conducive to improving the electrochemical performance of the ultrasonic product. The problems such as insufficient removal of residual alkali due to too small amount of acidic detergent, and difficulty in forming sufficient lithium-deficient state on the surface of the ultrasonic product, thereby affecting the rate performance of the positive electrode material, and the problems such as corrosion of the ultrasonic product or introduction of new impurities due to too large amount of acidic detergent can be basically avoided.
[0111] In some embodiments, the mass ratio of the coating agent to the calcined product is 0-0.05:1, specifically 0, 0.01:1, 0.02:1, 0.03:1, 0.04:1, 0.05:1, or any range between any two of them. Adding a small amount of coating agent helps to further stabilize the structure of the ultrasonic product, and the problem of affecting the conductivity of the target material due to too large amount of coating agent can be basically avoided.
[0112] In some embodiments, the solid-liquid ratio of the calcined product to water is 0.5-5:1, specifically 0.5-1.5:1. As an example, the solid-liquid ratio of the calcined product to water can be specifically 0.5:1, 0.8:1, 1:1, 1.2:1, 1.5:1, 2:1, 3:1, 4:1, 5:1, or any range between any two of them. The above solid-liquid ratio can make the calcined product fully dissociate and disperse, and at the same time the calcined product and water fully contact, thereby removing the residual alkali on the surface of the calcined product. The problems such as insufficient contact of the calcined product and water due to too large solid-liquid ratio of the calcined product to water, incomplete alkali removal, and water resource waste due to too small solid-liquid ratio of the calcined product to water can be basically avoided.
[0113] In some embodiments, the stirring paddle speed in the ultrasonic water washing container is 60 rad / min-600 rad / min, specifically 300 rad / min-500 rad / min, specifically 300 rad / min, 350 rad / min, 400 rad / min, 450 rad / min, 500 rad / min, etc. When the stirring paddle speed is within the above range, it helps to make the mixture in the ultrasonic water washing container in a uniform dispersion state, further improve the ultrasonic efficiency, and basically avoid the problems such as precipitation of the calcined product due to too low stirring paddle speed, thereby reducing the washing efficiency, and particle breakage due to too high stirring paddle speed.
[0114] In some embodiments, the ultrasonic power is 100 W to 3000 W, and specifically can be 1000 W to 2500 W. For example, the ultrasonic power can be 100 W, 500 W, 1000 W, 1200 W, 1400 W, 1600 W, 1800 W, 2000 W, 2200 W, 2400 W, 2500 W, 3000 W, or a range between any two of them. The ultrasonic power can effectively break the agglomeration of the calcined product, make the particles of the calcined product uniformly dispersed, and help to strengthen the water washing process to remove alkali, and basically avoid the problems of particle breakage caused by too high power, and incomplete dispersion of particles and incomplete removal of alkali caused by too low power.
[0115] In some embodiments, the ultrasonic frequency is 10 KHz to 50 KHz, and specifically can be 30 KHz to 45 KHz. For example, the ultrasonic frequency can be 10 KHz, 30 KHz, 32 KHz, 34 KHz, 36 KHz, 38 KHz, 40 KHz, 42 KHz, 44 KHz, 45 KHz, 50 KHz, or a range between any two of them. The ultrasonic frequency in the above range helps to further make the particles of the calcined product uniformly dispersed, and at the same time sufficiently remove alkali, and basically avoid the problems of particle breakage caused by too high frequency, and incomplete dispersion of particles and incomplete removal of alkali caused by too low frequency.
[0116] In some embodiments, the temperature of the ultrasonic treatment is 10℃ to 60℃, and specifically can be 20℃ to 40℃. For example, the temperature of the ultrasonic treatment can be 10℃, 20℃, 25℃, 30℃, 35℃, 40℃, 50℃, 60℃, or a range between any two of them. The ultrasonic temperature helps to further improve the ultrasonic efficiency, and make the agglomeration in the calcined product quickly dispersed, and at the same time further strengthen the water washing process to remove alkali.
[0117] In some embodiments, the time of the ultrasonic treatment is 10 min to 80 min, and specifically can be 20 min to 50 min. For example, the time of the ultrasonic treatment can be 10 min, 20 min, 25 min, 30 min, 35 min, 40 min, 45 min, 50 min, 60 min, 70 min, 80 min, or a range between any two of them. The above ultrasonic time basically ensures that the residual alkali on the surface of the calcined product is sufficiently removed, and the particles are completely and uniformly dispersed.
[0118] In some embodiments, the D 50 of the ultrasonic product is 1 μm to 10 μm, and specifically can be 1 μm to 6 μm, and more specifically can be 1.8 μm to 3.3 μm. For example, the D 50The micrometer size can be 1 μm, 1.2 μm, 1.5 μm, 1.8 μm, 2.0 μm, 2.2 μm, 2.4 μm, 2.6 μm, 2.8 μm, 3.0 μm, 3.2 μm, 3.3 μm, 4 μm, 5 μm, 6 μm, or any two of these ranges. The Do of the ultrasonic product... 50 Within the aforementioned range, it can be ensured that the particles of the subsequently prepared cathode material are close to those ranges, thereby giving the cathode material excellent structural stability and essentially avoiding D... 50 Excessive density slows down the diffusion rate of lithium ions in the cathode material, reducing the capacity of the lithium battery, and also affecting D. 50 If the particles are too small, they are more likely to agglomerate, which can hinder lithium-ion diffusion and affect battery performance.
[0119] In some embodiments, the compaction density of the ultrasonic product is 3.0 g / cm³. 3 ~3.65g / cm 3 Specifically, it can be 3.2 g / cm³. 3 ~3.55g / cm 3 As an example, the compaction density of the ultrasonic product can be 3.0 g / cm³. 3 3.1g / cm 3 3.2g / cm 3 3.3g / cm 3 3.4g / cm 3 3.5g / cm 3 3.6g / cm 3 3.65g / cm 3 Or a range between or any two of these. A compaction density of the ultrasonic product within the above range allows for the subsequent preparation of a cathode material with a high compaction density, thereby improving the energy density of lithium batteries using this cathode material.
[0120] S40: Mix the ultrasonic product and the coating agent to obtain a second mixture.
[0121] In this step, a certain amount of coating agent can be added to the ultrasonic product and mixed evenly to obtain a second mixture. There are no particular restrictions on the mixing method; for example, a mixer or grinding can be used for mixing.
[0122] Specifically, the specific types of coating agents can be the same as described above, and will not be repeated here.
[0123] In some embodiments, M in the coating agent 2 The molar ratio of the element to the nickel-cobalt-manganese precursor is 0–0.03:1, specifically 0.001–0.018:1. As an example, M in the coating agent… 2The molar ratio of the element to the nickel-cobalt-manganese precursor can be specifically 0.001:1, 0.005:1, 0.01:1, 0.012:1, 0.014:1, 0.016:1, 0.018:1, 0.02:1, 0.03:1, or a range between any two of them. The addition of the coating agent in the above range helps to obtain a positive electrode material with a more stable structure through subsequent sintering.
[0124] S50: performing secondary low-temperature sintering on the second mixture to obtain the positive electrode material.
[0125] In this step, the second mixture obtained above can be subjected to secondary low-temperature sintering under an air or oxygen atmosphere from room temperature to 300-650°C, and then cooled to room temperature after sintering for 3-12 hours to obtain the positive electrode material.
[0126] In some embodiments, the heating rate of the secondary low-temperature sintering is 1-10°C / min, and can be specifically 2-6°C / min. As an example, the heating rate of the secondary low-temperature sintering can be specifically 1°C / min, 2°C / min, 3°C / min, 4°C / min, 5°C / min, 6°C / min, 7°C / min, 8°C / min, 9°C / min, 10°C / min, or a range between any two of them. The above heating rate helps to gradually transfer the heat inside the second mixture, making the temperature of each part of the second mixture uniform, thereby helping the reaction to proceed smoothly, and basically avoiding the particle breakage caused by the local temperature being too high due to the heating rate being too fast, reducing the structural stability of the positive electrode material, and the time waste caused by the heating rate being too slow.
[0127] In some embodiments, the sintering temperature of the secondary low-temperature sintering is 300-650°C, and can be specifically 350-500°C. As an example, the sintering temperature of the secondary low-temperature sintering can be 300°C, 350°C, 400°C, 450°C, 500°C, 550°C, 600°C, 650°C, or a range between any two of them. The above temperature range helps the second mixture to react completely, the coating agent to form a coating layer on the surface of the ultrasonic product, and the positive electrode material to obtain a stable structure, and basically avoids the cost waste caused by the temperature being too high and the second mixture not reacting sufficiently caused by the temperature being too low.
[0128] In some embodiments, the sintering time of the secondary low-temperature sintering is 3h-12h, and specifically can be 5h-10h. For example, the sintering time of the secondary low-temperature sintering can be 3h, 4h, 5h, 6h, 7h, 8h, 9h, 10h, 11h, 12h or a range between any two of them. The above time can basically ensure that the reaction is sufficient, and a stable structure of the positive electrode material is obtained, and problems such as insufficient reaction caused by too short time and time cost waste caused by too long time can be basically avoided.
[0129] The positive electrode material prepared by the above method has the following advantages:
[0130] 1. The primary product after high-temperature sintering is in an irregular agglomerated state, which is fully dissociated under the action of ultrasonic water washing, which helps to obtain a positive electrode material with high dispersion and highly concentrated particle size distribution. At the same time, the particles will not collide excessively during the preparation process, which helps to make the particles round and smooth, and has a high compaction density.
[0131] 2. Ultrasonic water washing can not only avoid the generation of fine powder caused by excessive surface residual alkali of the product, but also remove the excess residual alkali on the surface of the particles under the action of the aqueous solution, which helps to make the surface structure of the positive electrode material more stable and improve the processing performance and safety.
[0132] 3. The positive electrode material particle surface is smooth and has a high compaction density. During electrochemical reaction, it can fully contact with the electrolyte and Li ion to be more fully deintercalated, which helps to improve the charge and discharge capacity and rate performance of the lithium battery. In the water washing and dissociation process, an auxiliary agent can be used for surface modification, which further reduces the residual alkali and at the same time can exchange protons with the positive electrode particle surface, so that the particle surface is in a lithium-deficient state, and the structural stability, first coulombic efficiency and rate performance of the positive electrode material are improved.
[0133] 4. The yield of the positive electrode material dissociation is improved, which can theoretically reach 100%, and the process is simple, the energy consumption is low, and it is easy to industrialize production.
[0134] In the third aspect of the present application, a lithium battery is provided, which comprises the above positive electrode material. Therefore, the lithium battery has high energy density, excellent stability and safety performance, including thermal stability, cycle stability, etc.
[0135] In some embodiments, the lithium battery can include a positive electrode sheet, a negative electrode sheet, and a separator, all of which are soaked in an electrolyte. During the charging and discharging of the battery, active ions are inserted and extracted between the positive electrode sheet and the negative electrode sheet. The electrolyte serves as an ion conductor between the positive electrode sheet and the negative electrode sheet. The separator is disposed between the positive electrode sheet and the negative electrode sheet to prevent short circuiting between the positive electrode sheet and the negative electrode sheet, and to allow the active ions to pass through.
[0136] In some embodiments, the positive electrode sheet includes a positive electrode current collector and a positive electrode active material layer disposed on at least one side of the positive electrode current collector. The positive electrode active material layer includes the positive electrode material described herein. As such, the lithium battery has excellent cycle stability and thermal stability.
[0137] In some embodiments, the positive electrode current collector can be a metal current collector or a composite current collector. For example, the metal current collector can include, but is not limited to, an aluminum foil current collector. The composite current collector can include a polymer material base layer and a metal layer formed on at least one surface of the polymer material base layer. The composite current collector can be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver, and silver alloy, etc.) on a polymer material base layer (such as a base layer of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0138] In some embodiments, in addition to the positive electrode material described above, the positive electrode active material layer can further include a conductive agent, a binder, and necessary additives, etc.
[0139] In some embodiments, the binder in the positive electrode active material layer can include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), a vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, a vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, a tetrafluoroethylene-hexafluoropropylene copolymer, and a fluorine-containing acrylic ester-based resin.
[0140] In some embodiments, the conductive agent in the positive electrode active material layer can include at least one of super-conductive carbon, conductive graphite, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0141] In some embodiments, the negative electrode sheet can include a negative electrode current collector and a negative electrode active material layer disposed on at least one side surface of the negative electrode current collector. As an example, the negative electrode active material layer can include a negative electrode material, a thickening agent, a conductive agent, and a binder.
[0142] Specifically, the negative current collector can adopt a metal foil, for example, the metal foil can adopt a copper foil. The negative material can include a carbon-based material, a silicon-based material, a tin-based material, etc. The binder in the negative material layer can include, but is not limited to, at least one of styrene butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA), and carboxymethyl chitosan (CMCS). The conductive agent in the negative material layer can include, but is not limited to, at least one of super conductive carbon, acetylene black, carbon black, ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0143] In some embodiments, the separator can adopt a separator that is commonly known in the art and can be used for lithium ion batteries and is stable to the electrolyte used, such as a polyethylene separator, a polypropylene separator, a polyethylene / polypropylene composite separator, etc.
[0144] In a fourth aspect of the present application, a power consuming device is provided, which comprises the positive material as described above or the lithium battery as described above. Thus, the power consuming device has all the features and advantages of the positive material or the lithium battery as described above, which will not be repeated here.
[0145] According to embodiments of the present application, the specific type of the power consuming device is not particularly limited and can be any device that adopts a lithium battery as a power source or an energy storage unit. As examples, the power consuming device includes, but is not limited to, an electric vehicle (such as a pure electric vehicle, a hybrid electric vehicle, a plug-in hybrid electric vehicle, an electric bicycle, an electric scooter, an electric golf cart, an electric truck, etc.), a mobile terminal (such as a mobile phone, a notebook computer, a game console, a wearable device, etc.), a drone, an aerospace device, a satellite, a ship, an energy storage system, etc.
[0146] It can be understood that, in addition to the lithium battery as described above, the power consuming device further includes other necessary structures and components, which can be referred to conventional technologies, for example, an electric vehicle can include a vehicle body, a chassis, tires, a navigation system, a radar system, a steering system, a braking system, a lubrication system, a cooling system, a driving system, etc., which will not be repeated here.
[0147] The present application will be described below with reference to specific examples, it should be noted that these examples are merely descriptive and do not limit the present application in any way. If the specific techniques or conditions are not specified in the examples, they are performed according to the techniques or conditions described in the literature in the art or according to the product instructions.
[0148] Example 1
[0149] The positive material is prepared as follows:
[0150] S10: three kinds of salts of NiSO4·6H2O, CoSO4·7H2O and MnSO4·H2O are prepared into a mixed salt solution of metal ions with a concentration of 2 mol / L according to a molar ratio of Ni:Co:Mn of 15:1:4, a NaOH solution with a concentration of 4 mol / L is prepared as a precipitant, and an ammonia water solution with a concentration of 0.8 mol / L is prepared as a complexing agent;
[0151] The prepared mixed salt solution of metal ions, the precipitant and the complexing agent are added into a reaction kettle with nitrogen as a protective gas to generate a precipitation reaction, the pH of the reaction is controlled to be 11.6, the stirring rate is 600 rad / min, the reaction temperature is 50℃, and after 21 h of reaction, a precipitate is obtained, the precipitate is then filtered, washed and dried at 100℃ for 10 h to obtain a nickel-cobalt-manganese precursor powder with a composition of Ni 0.75 Co 0.05 Mn 0.2( OH)2.
[0152] The nickel-cobalt-manganese precursor powder, LiOH and the dopant Al2O3 are uniformly mixed in a high-speed mixer according to a molar ratio of 1:1.06:0.005 to obtain a first mixture.
[0153] S20: the first mixture is subjected to primary sintering in an oxygen atmosphere, is heated from room temperature to 950℃ at a heating rate of 3℃ / min, is sintered for 9 h, and is then cooled to room temperature to obtain a primary sintered product.
[0154] S30: the primary sintered product is mixed with pure water according to a solid-liquid ratio of 1:1, is added into an ultrasonic washing container, the stirring paddle of the ultrasonic washing container rotates at a speed of 450 rad / min, the ultrasonic power is 800 W, the ultrasonic frequency is 35 KHz, the ultrasonic washing time is 30 min, and the water temperature in the ultrasonic washing container is 25℃, the mixture after ultrasonic treatment is filtered, the filter residue is washed and dried to obtain an ultrasonic product with high dispersity.
[0155] S40: the ultrasonic product is uniformly mixed with a coating agent B2O3 according to a molar ratio of 1:0.0015 to obtain a second mixture.
[0156] S50: the second mixture is subjected to secondary low-temperature sintering in an air atmosphere, is heated from room temperature to 350℃ at a heating rate of 3℃ / min, is sintered for 7 h, and is then cooled to room temperature to obtain a positive electrode material with a chemical formula of Li 1.06 (Ni 0.75 Co 0.05 Mn 0.2 Al 0.005 B 0.0015 )O2.
[0157] The positive electrode material prepared above is made into a positive electrode, lithium metal is used as a negative electrode, a separator is a polyimide composite separator, and an electrolyte is 25% lithium hexafluorophosphate with a concentration of 1 mol / L, 40% ethylene carbonate, 30% dimethyl carbonate, and 5% fluoroethylene carbonate. A coin-type half battery is prepared, wherein the positive electrode comprises an aluminum foil and a positive electrode active material layer arranged on both sides of the aluminum foil, and the positive electrode active material layer comprises the positive electrode material prepared above, a conductive agent acetylene black, and a binder PVDF in a mass ratio of 95:3:2.
[0158] Examples 2-19
[0159] The same as Example 1, and the specific differences are shown in Tables 1-2.
[0160] Comparative Example 1
[0161] S10: Three kinds of salts of NiSO4·6H2O, CoSO4·7H2O, and MnSO4·H2O are prepared into a mixed metal ion salt solution with a concentration of 2 mol / L according to a molar ratio of Ni:Co:Mn of 15:1:4, a 4 mol / L NaOH solution is prepared as a precipitant, and a 0.8 mol / L ammonia solution is prepared as a complexing agent.
[0162] The prepared mixed metal ion solution, precipitant, and complexing agent are added to a reaction kettle with nitrogen as a protective gas to undergo a precipitation reaction, the pH of the reaction is controlled at 11.6, the stirring rate is 600 rad / min, the reaction temperature is 50°C, and after 21 h of reaction, a precipitate is obtained. The precipitate is filtered, washed, and dried at 100°C for 10 h to obtain a nickel-cobalt-manganese precursor powder with a composition of Ni 0.75 Co 0.05 Mn 0.2( OH)2.
[0163] The nickel-cobalt-manganese precursor powder, LiOH, and the dopant WO3 are mixed uniformly in a high-speed mixer according to a molar ratio of 1:1.05:0.008 to obtain a first mixture.
[0164] S20: The first mixture is subjected to a first sintering in an oxygen atmosphere, heated from room temperature to 955°C at a heating rate of 3°C / min, sintered for 9 h, and then cooled to room temperature to obtain a first sintered product.
[0165] S30: The first sintered product is broken using a fluidized bed jet mill, the feeding classification is 20 Hz, the classification wheel frequency is 40 Hz, the grinding gas pressure is 350 KPa, the induced air pressure is -10 KPa, and a broken product is obtained after breaking.
[0166] S40: The broken product is mixed with the coating agent Sr(OH)2in a molar ratio of 1:0.005 to obtain a second mixture.
[0167] S50: The second mixture is subjected to secondary low-temperature sintering in an air atmosphere, heated from room temperature to 350°C at a heating rate of 3°C / min, sintered for 7h, and then cooled to room temperature to obtain a positive electrode material with a chemical formula of Li 1.05 (Ni 0.75 Co 0.05 Mn 0.2 W 0.008 Sr 0.005 )O2.
[0168] Comparative Example 2
[0169] The preparation process is basically the same as that of Comparative Example 1, except that the first sintered product is broken using a fluidized bed jet mill, the feeding classification is 20Hz, the classification wheel frequency is 70Hz, the grinding gas pressure is 350KPa, the induced air pressure is -10KPa, and the broken product is obtained after breaking.
[0170] Performance Test
[0171] The particle size of the positive electrode material prepared in Examples 1-19 and Comparative Examples 1-2 and the battery is tested for the first charge-discharge specific capacity, the first charge-discharge efficiency, the discharge specific capacity, the battery rate, and the capacity retention rate, and the test method is as follows:
[0172] The particle size of the positive electrode material is measured by LIBMAS analysis software for single crystal particles, and the SEM test requires that the particles be randomly sampled when the sample is prepared, and randomly photographed when the test is performed. In order to ensure the stability of the test and facilitate the measurement, the SEM is photographed at any multiple of 2K-6K, and at least 600 particles are randomly taken, and the average value of the caliper diameter is tested, which is equal to the average value of the length and width of the smallest circumscribed rectangle of the positive electrode material particles.
[0173] The particle size of the positive electrode material is D 50 , D 95 , D5, D1, D 99 , which are all tested by a laser particle size analyzer of Mastersizer 3000 model of Marvern Company by wet method.
[0174] The first charge-discharge specific capacity and the first coulombic efficiency of the battery are tested by charging from 3.0V to 4.45V at a constant current of 0.1C and a constant voltage, and discharging to 3V at a constant current of 0.1C, to obtain the first charge-discharge specific capacity and the first coulombic efficiency of the battery at 0.1C.
[0175] Battery discharge specific capacity: charge from 3.0 V to 4.45 V at a constant current of 0.33 C and a constant voltage, cut off current 0.05 C, then discharge to 3 V at a constant current of 0.33 C, and test the discharge specific capacity of 0.33 C.
[0176] High-temperature cycle capacity retention: charge from 3.0 V to 4.45 V at a constant current of 1 C in a 45℃ constant temperature oven, then discharge to 3 V at a constant current of 1 C, and test the high-temperature cycle capacity retention of the material after 80 cycles of charge and discharge.
[0177] Test results
[0178] The scanning electron microscope image of the positive electrode material prepared in Example 2 is shown in Figure 2 It can be seen that the particles are uniformly dispersed, and the particle size of the particles is relatively concentrated.
[0179] The particle size distribution graph of the positive electrode material prepared in Example 2 is shown in Figure 3 It can be seen that the particle size distribution is highly concentrated, and the distribution range is narrow.
[0180] The scanning electron microscope image of the positive electrode material prepared in Comparative Example 2 is shown in Figure 4 It can be seen that the particle dispersion uniformity is slightly poor, and the particle size of the particles is greatly different.
[0181] The particle size distribution graph of the positive electrode material prepared in Comparative Example 2 is shown in Figure 5 It can be seen that the particle size distribution range is wide.
[0182] Table 1: Preparation parameters of positive electrode material
[0183]
[0184] Table 2: Performance parameters of positive electrode material
[0185]
[0186]
[0187] Table 3: Performance parameters of battery
[0188]
[0189]
[0190] From the above data, it can be seen that the positive electrode material of the present application can significantly improve the first charge and discharge capacity and efficiency of the battery, and the rate performance and cycle performance of the battery are also significantly improved.
[0191] In addition, the terms "first", "second", etc. are used only for the purpose of description, and should not be understood as indicating or implying relative importance or a specific number of the technical features indicated. Therefore, the features defined as "first", "second" can explicitly or implicitly include at least one of the features. In the description of the present application, the meaning of "a plurality of" is at least two, for example, two, three, etc., unless otherwise explicitly and specifically limited.
[0192] In the description of the present application, the description referring to the terms "one embodiment", "some embodiments", "an example", "a specific example", or "some examples" and the like means that the specific features, structures, materials or characteristics described in connection with the embodiment or example are included in at least one embodiment or example of the present application. In the present specification, the illustrative description of the above terms does not necessarily refer to the same embodiment or example. Also, the specific features, structures, materials or characteristics described can be combined in any appropriate manner in any one or more embodiments or examples. In addition, the person skilled in the art can combine and combine the different embodiments or examples described in the present specification and the features of the different embodiments or examples, without contradiction.
[0193] Although the embodiments of the present application have been shown and described above, it is understood that the above-described embodiments are exemplary and should not be construed as limiting the present application, and those skilled in the art can make changes, modifications, replacements and variations to the above-described embodiments within the scope of the present application.
Claims
1. A positive electrode material, characterized by, comprising a compound represented by the following formula: Li n (Ni x Co y Mn z M 1-x-y-z )O2 wherein 0.95≤n≤1.15, 0.96≤x+y+z≤1, M is at least one of Al, Ce, Fe, P, W, Co, Mo, Sr, Sb, Ta, Nb, Y, Mg, Ti, Zr; and satisfies: 1.01≤I 50 = D 50 / p≤1.4; D1≥1.3μm, the particle size p of the positive electrode material is an average value of the caliper diameter measured in the SEM image under the scale.
2. The positive electrode material of claim 1, wherein, the positive electrode material satisfies: 1.01≤I 50 = D 50 / p≤1.25; preferably 1.01≤I 50 = D 50 / p≤1.15; D1≥1.4μm.
3. The cathode material of claim 1, wherein, The positive electrode material satisfies: 0.1≤K 95 =(D 95 -D5) / D 50 ≤1.1, preferably 0.3≤K 95 =(D 95 -D5) / D 50 ≤1.0; more preferably 0.6≤K 95 =(D 95 -D5) / D 50 ≤0.
9.
4. The cathode material of claim 1, wherein, the agglomeration rate of the positive electrode material is ≤8%, wherein the agglomeration rate is a ratio of the number of particles with the number of agglomerated particles ≥3 to the total number of particles.
5. The cathode material of claim 1, wherein, the particle size p of the positive electrode material and the particle size distribution S P satisfies: 0.86 ≤ S P = S (p-p / 2,p+p / 2) ≤ 1, preferably 0.92 ≤ S P = S (p-p / 2,p+p / 2) ≤ 1, more preferably 0.96 ≤ S P = S (p-p / 2,p+p / 2) ≤ 0.99; where S P is the proportion of particles having a particle size distribution within the range (p-p / 2, p+p / 2).
6. The cathode material of claim 1, wherein, the positive electrode material satisfies at least one of the following conditions: D 99 satisfies: D 99 ≤ 5.5 pm, preferably D 99 ≤ 4.5 pm; D50 of the positive electrode material is 1 μm to 10 μm, preferably 1 μm to 5 μm, more preferably 1.6 μm to 3.0 μm. 50 D50 of the positive electrode material is 1 μm to 10 μm, preferably 1 μm to 5 μm, more preferably 1.6 μm to 3.0 μm. the particle size p of the positive electrode material satisfies 0.1μm≤p≤10μm, preferably 0.5μm≤p≤6μm, more preferably 1μm≤p≤2.4μm; The compacted density of the positive electrode material is 3.0 g / cm 3 ~ 3.75 g / cm 3 ; preferably 3.2 g / cm 3 ~ 3.65 g / cm 3 ; the alkali content of the positive electrode material is ≤10000ppm, preferably the alkali content is ≤6000ppm, more preferably the alkali content is ≤4000ppm.
7. The cathode material of claim 1, wherein, at least one of the following conditions is satisfied: 1.01≤n≤1.09; 0.97≤x+y+z≤1; 0.6≤x≤0.98; 0.03≤y≤0.15; 0.1≤z≤0.3。 8. A method for producing the positive electrode material according to any one of claims 1 to 7, characterized by, comprising: mixing a nickel-cobalt-manganese precursor, a lithium source and optionally a dopant to obtain a first mixture; sintering the first mixture once to obtain a one-sintered product; mixing the one-sintered product with water and performing ultrasonic treatment under stirring and drying to obtain an ultrasonic product; mixing the ultrasonic product with a coating agent to obtain a second mixture; sintering the second mixture at a low temperature for the second time to obtain the positive electrode material; The dopant contains M 1 The M 1 The M includes at least one of Al, Ce, Fe, P, B, W, Sr, Y, Mg, Ti, and Zr. The coating agent contains M 2 The element M 2 The element includes at least one of Al, W, Co, Mo, B, Sb, Ta, Nb, Mg, Ti.
9. The method of claim 8, wherein, at least one of the following conditions is satisfied for the one-sintering: the heating rate of the one-sintering is 1℃ / min~10℃ / min, preferably 2℃~6℃ / min; the sintering temperature of the one-sintering is 700℃~1100℃, preferably 750℃~980℃; the sintering time of the one-sintering is 3h~15h, preferably 6h~12h.
10. The method of claim 8, wherein, mixing the one-sintered product with water and an auxiliary agent and then performing the ultrasonic treatment and the drying in sequence to obtain the ultrasonic product.
11. The method of claim 10, wherein, at least one of the following conditions is satisfied for the ultrasonic treatment: the solid-liquid ratio of the one-sintered product to water is 0.5~5:1, preferably 0.5~1.5:1; the ultrasonic power is 100W~3000W, preferably 1000W~2500W; the ultrasonic frequency is 10KHz~50KHz, preferably 30KHz~45KHz; the temperature of the ultrasonic treatment is 10℃~60℃, preferably 20℃~40℃; the time of the ultrasonic treatment is 10min~80min, preferably 20min~50min; the stirring paddle speed is 60rad / min~600rad / min, preferably 300rad / min~500rad / min; the auxiliary agent comprises at least one of an acidic detergent and the coating agent; the acidic detergent comprises at least one of hydrochloric acid, phosphoric acid, metaphosphoric acid, oxalic acid and salts thereof, preferably comprises at least one of hydrochloric acid, phosphoric acid, metaphosphoric acid, oxalic acid, sodium oxalate, ammonium metaphosphate, diammonium hydrogen phosphate, ammonium dihydrogen phosphate; The molar ratio of the acidic detergent to the one-fired product is 0.0001-0.005:1; The mass ratio of the coating agent to the one-fired product is 0-0.05:
1.
12. The method of claim 8, wherein, The ultrasonic product satisfies at least one of the following conditions: The D of the ultrasonic product 50 The micrometer size is 1 μm to 10 μm, preferably 1 μm to 6 μm, and more preferably 1.8 μm to 3.3 μm. The compacted density of the ultrasonic product is 3.0 g / cm 3 ~ 3.65 g / cm 3 , preferably 3.2 g / cm 3 ~ 3.55 g / cm 3 .
13. The method of claim 8, wherein, The secondary low-temperature sintering satisfies at least one of the following conditions: The heating rate of the secondary low-temperature sintering is 1-10 ℃ / min, preferably 2-6 ℃ / min; The sintering temperature of the secondary low-temperature sintering is 300-650 ℃, preferably 350-500 ℃; The sintering time of the secondary low-temperature sintering is 3-12 h, preferably 5-10 h.
14. The method of claim 8, wherein, At least one of the following conditions is satisfied: The nickel cobalt manganese precursor includes Ni x Co y Mn z( OH)2; The D50 of the nickel cobalt manganese precursor is 1 μm to 5 μm, preferably 2.4 μm to 3.9 μm. 50 The D50 of the nickel cobalt manganese precursor is 1 μm to 5 μm, preferably 2.4 μm to 3.9 μm. The BET of the nickel cobalt manganese precursor is 6m 2 / g ~ 20m 2 / g, preferably 8m 2 / g ~ 15m 2 / g; tap density of the nickel cobalt manganese precursor is 0.5 g / cm 3 ~ 5 g / cm 3 , preferably 1 g / cm 3 ~ 3 g / cm 3 ; The lithium source includes at least one of LiOH, Li2CO3, Li2SO4, and LiCl; The molar ratio of the nickel-cobalt-manganese precursor to the lithium source is 1:0.95-1.15, preferably 1:1.01-1.09; The dopant comprises M 1 at least one of an oxide and a hydroxide of an element, preferably at least one of aluminum oxide, aluminum hydroxide, boron oxide, tungsten oxide, strontium oxide, yttrium oxide, zirconium oxide, titanium oxide, magnesium oxide; M in the dopant 1 the molar ratio of the element to the nickel cobalt manganese precursor is 0-0.03:1, preferably 0.001-0.02:1; The coating agent includes the M 2 at least one of an oxide, a hydroxide, a sulfate, an oxalate of an element, preferably at least one of aluminum oxide, aluminum hydroxide, boron oxide, boric acid, cobalt oxide, cobalt tetraoxide, cobalt hydroxide, tungsten oxide, tungstic acid, magnesium hydroxide; M in the coating agent 2 The molar ratio of the element to the nickel-cobalt-manganese precursor is 0-0.03:1, preferably 0.001-0.018:
1.
15. A lithium battery, characterized by The positive electrode material includes any one of the positive electrode materials in claims 1-7.
16. An electrical device, comprising: The lithium battery includes any one of the positive electrode materials in claims 1-7 or the lithium battery in claim 15.
Citation Information
Patent Citations
Transition metal oxide positive electrode material of single crystal type lithium and preparation method and application thereof
CN112830524A
High-nickel NCM ternary positive electrode material with surface coated with multiple substances simultaneously and application of high-nickel NCM ternary positive electrode material
CN114975914A
Positive electrode material, preparation method thereof and lithium ion battery
CN117936771A
Single-crystal-type multi-element positive electrode material, and preparation method therefor and application thereof
WO2022207008A1
Cited By
Monocrystal ternary positive electrode material, preparation method thereof and positive electrode slurry
CN121617902A